POSICIÓN SISTEMÁTICA Y REDESCRIPCIÓN DE SCAPTIA (PSEUDOMELPIA) HORRENS ENDERLEIN, 1925 (DIPTERA: TABANIDAE: PANGONIINAE) (Acta Entomológica Chilena, 2022)
The subgenus Pseudomelpia Enderlein composed by only one known species from Southern Chile isredefined, and a new key and comments for subgenera of Scaptia Walker of Australasian and Neotropicaldistribution is offered.